Ownership and voting power in France - Laurence Bloch; Elizabeth Kremp (Fondazione Eni Enrico Mattei (FEEM), 1999)
This paper provides an overview on ownership structure and voting power in France, both in terms of institutional and legal framework and of quantitative analysis. If cross share holdings in large groups were a characteristic of the French model, called «financial core», and had been extended in 1986, with the first wave of privatisations, the foundations of this model seem to be weakened. This organisation has not been able to really prevent the increasing of foreign presence in French capitalisation. Looking at listed firms and CAC40 firms, and at a large data set of unlisted firms, this paper shows that concentration of direct ownership and voting power is very high in France, even for listed and CAC40 firms. The second direct owner lags far behind the first one and the category «families» plays a major role in the detention of non-listed firms. The average ownership stakes of banks, insurance companies and other financial institutions are relatively low, except for CAC40 firms.
Keywords: G32; G34; 330; Block shareholdings in France; shareholder voting power; ownership; listed and unlisted firms; Eigentümerstruktur; Frankreich; Aktienstimmrecht